Spatial Variability of Selected Soil Properties in Long-Term Drained and Restored Peatlands - Negassa, Wakene; Baum, Christel; Beyer, Florian; Leinweber, Peter (Frontiers in Environmental Science, 2022)
Drained peatlands have been rewetted for restoration in Europe and North America for about 25 years. However, information on spatial variability of soil chemical and biochemical properties in long-term drained and restored peatlands is insufficient to design appropriate research methods and soil sampling protocols for monitoring biogeochemical processes. The study aimed to examine the influence of long-term drainage and rewetting of peatlands on smallscale spatial variability of the soil chemical properties and enzyme activities. We collected 400 soil samples from the 0–15 cm and 15–30 cm soil depths of a drained and a corresponding rewetted peatland. The number of grid cells was 100 for each of the drained and the rewetted peatland, and the size of each grid cell was 3 m × 3 m. We analyzed 17 soil parameters from the surfaces and 14 from the subsurface of both sites. The variability (range, SD, and CV) of all the soil properties was higher in the drained peatland than in the restored peatlands except for the soil pH. The geostatistical analysis revealed only the soil pH, acid phosphatase, β-glucosidase, and arylsulfatase activities disclosed the strong spatial dependency at the ≤5 m semivariance range in the drained peatland. However, more than 80% of the soil properties showed a strong spatial dependence within the 4–20 m semivariance ranges in the restored peatland. The strong spatial dependencies of all the soil properties in the long-term restored peatland conclusively call for the spatial soil sampling and geostatistical data analysis methods to capture substantial spatial variability that has important implications in degraded peatland restoration.